(untitled) (Journal of Economic Research & Business Administration, 2018)
Tourism is one of the most successful and dynamically developing sectors of the world economy. This is evidenced by the share of tourism (about 10%) in world GDP. Being the most successful business in the world, tourism is the most important source of the state budget. The article examines the current state of tourism in the digital economy and its contribution to the economy. Particular attention is paid to changes and innovations in the field of digital economy. The purpose of the article is to reveal the advantages of the development of digital tourism and the prospects for its development. New opportunities in tourism in the digital economy are analyzed. In the development of digital tourism, this is directly related to the fact that today’s world community can’t be imagined without any portable technical devices. The development of tourism in the digital economy will help to strengthen competition between states, improve people’s well-being and provide jobs. Tourism also solves social problems associated with preserving traditional opportunities and balancing international partnerships between states.